Calendario : Concurso de dibujos calendario SCA 2007 (2007)
Dibujos premiados.
Keywords: DUSSERRE, FLORENCIA; NAHUM, RODRIGO; FRIDMAN, VICTOR; NAVONE, GUSTAVO; LEVINTON, LUCIANA; LÓPEZ, DAVID; GARRIDO, FEDERICO; EIGUCHI, ADRIÁN; BÁEZ, OSCA; RNERPITI, VALERIA; IGLESIAS DEMICHELI, EMILIANA; PÉREZ, FLORENCIA; ARGENTINA; CONCURSOS; PREMIOS; ALMANAQUES; DIBUJOS